SEARCHING DISTRIBUTED DATA WITH MULTI AGENT SYSTEM - Vishal D. Lipte; Sandip A. Shivarkar; Ajit A. Muzumda; Pravinkumar B. Landge (International Journal of Innovations in Engineering Research and Technology, 2021)
In distributed systems, to search out information is costly task because they have to be compel led to transfer information from node containing information to the node wherever query is generated, this will l consume latency, network traffic etc.For reducing these parameters mobile agents are accustomed fetch information from nodes wherever information resides. Alongside mobile agents directory containing information concerning database kept on completely different nodes is employed to focus retrieval method solely to those nodes that are containing answers to the query. 3 kinds of agents areaunit accustomed fetch data specifically ly coordinator, search and local agent.